Oxygen Transport to Tissue XXXIII - Wolf, Martin; Bucher, Hans Ulrich; Rudin, Markus; Van Huffel, Sabine; Wolf, Ursula; Bruley, Duane F.; Harrison, David K. (Advances in Experimental Medicine and Biology, 2012)
Based on the 38th annual conference of the International Society on Oxygen Transport to Tissue (ISOTT), held in Ascona, Switzerland in July 2010, this volume covers all aspects of oxygen transport from air to the cells, organs and organisms; instrumentation and methods to sense oxygen and clinical evidence. It covers near infrared spectroscopy, brain oxygenation, tumor biology, angiogenesis and mitochondrial metabolism, systems modeling, gas transport, hypoxic adaptation and exercise physiology. Emphasis is placed on methods of oxygen measurement in living tissue and application of these technologies to understanding physiological and biological bases for pathology related to tissue oxygenation. This multidisciplinary volume includes contributions from scientists (physicists, biologists and chemists), engineers, clinicians and mathematicians.